THE POTENTIAL OF KELAKAI (STENOCHLAENA PALUSTRIS) AS A NATURAL GALACTAGOGUE IN INDONESIA: A LITERATURE REVIEW - Haulaini, Shahiroh (Journal Pharmacy Of Tanjungpura, 2026)
Stunting remains a major nutritional problem in Indonesia, and successful breastfeeding is one of the key strategies for its prevention. Kelakai (Stenochlaena palustris) is a local plant traditionally used by the community and is considered to have potential as a galactagogue. This study aimed to examine the potential of kelakai as a galactagogue in Indonesia based on previous studies. A literature review method was used by searching articles through the GARUDA and Scopus databases, supported by Scopus AI, using the keywords: Kelakai, Kalakai, Stenochlaena palustris, lactation, breastfeeding, breast milk, milk production, galactagogue, and Indonesia. The initial search identified 198 articles from GARUDA and 42 articles from Scopus. After the selection process, 3 main articles and 10 supporting articles were included. The review findings indicate that kelakai has potential as a galactagogue, as several direct studies on breastfeeding and postpartum mothers report increased breast milk volume or production after kelakai administration in the form of juice, pudding, and herbal tea. Supporting studies also show that kelakai contains iron, flavonoids, saponins, tannins, and other bioactive compounds that may contribute to maternal health. Therefore, kelakai is a promising local plant as a galactagogue, although further studies with stronger designs are still needed.